Implementasi Model Discovery-Brainstorming Learning Dalam Meningkatkan Kreatifitas Dan Jiwa Nasionalisme Siswa Pada Mata Pelajaran Pendidikan Agama Hindu Dan Budi Pekerti Di SMA Negeri 1 Bontang - Ni Made Adnyani (Kamaya: Jurnal Ilmu Agama, 2018)
The series of activities undertaken in two cycles consists of planning, execution, observation and reflection. The result showed that there was an increase of students' creativity in learning by 86.86% in the second cycle compared to 74.13% in the previous cycle. This increase is also directly visible in the use of various learning media to explore and learn various things that can increase the sense of empathy, openness, and tolerance to various problems from the original 81.66% to 91.67%. The results of this study indicate that the learning model of Discovery-Brainstorming Learning can improve the creativity and soul of students on the subjects of Hindu and Budi Pekerti Religion in SMA Negeri 1 Bontang. This learning model proved effective for small classes.